2012
DOI: 10.1371/journal.pone.0048577
|View full text |Cite
|
Sign up to set email alerts
|

Honeybees (Apis mellifera) Learn Color Discriminations via Differential Conditioning Independent of Long Wavelength (Green) Photoreceptor Modulation

Abstract: BackgroundRecent studies on colour discrimination suggest that experience is an important factor in how a visual system processes spectral signals. In insects it has been shown that differential conditioning is important for processing fine colour discriminations. However, the visual system of many insects, including the honeybee, has a complex set of neural pathways, in which input from the long wavelength sensitive (‘green’) photoreceptor may be processed either as an independent achromatic signal or as part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Our results thus confirm findings from experiments in which freeflying bees were trained to discriminate a visual target paired with sucrose solution from one or various visual distracters paired with quinine solution, under the assumption that quinine would act as a strong penalty favoring learning and discrimination (Chittka et al, 2003;Dyer and Chittka, 2004;Avargues-Weber et al, 2010;Reser et al, 2012;Avargues-Weber and Giurfa, 2014). In our experiments, bees did not fly within the small Y-maze, but as in the works just mentioned, they could move, explore the maze and compare the odor stimuli and their corresponding outcomes through sampling.…”
Section: Negative Reinforcements In Olfactory Learning In the Y-mazesupporting
confidence: 87%
“…Our results thus confirm findings from experiments in which freeflying bees were trained to discriminate a visual target paired with sucrose solution from one or various visual distracters paired with quinine solution, under the assumption that quinine would act as a strong penalty favoring learning and discrimination (Chittka et al, 2003;Dyer and Chittka, 2004;Avargues-Weber et al, 2010;Reser et al, 2012;Avargues-Weber and Giurfa, 2014). In our experiments, bees did not fly within the small Y-maze, but as in the works just mentioned, they could move, explore the maze and compare the odor stimuli and their corresponding outcomes through sampling.…”
Section: Negative Reinforcements In Olfactory Learning In the Y-mazesupporting
confidence: 87%
“…The role of brightness as a visual cue has been previously investigated using behavioural experiments (Lunau and Maier 1995;Giurfa et al 1996;Kelber 2005) and, therefore, might be an important visual signal in bee-pollinated flowers. Brightness perception is the ability to perceive stimulus intensity differences (Wyszecki and Stiles 1982;Reser et al 2012), where intensity is related to the total amount of energy reflected by a stimulus. To understand whether intensity is a meaningful signal for bee pollinators it is important to test visual perception while isolating other confounding chromatic cues (Reser et al 2012).…”
Section: Open Accessmentioning
confidence: 99%
“…For subsequent analyses it was important to reduce factors based upon the biological plausibility of cause. Studies on honeybee vision suggest brightness is not a major perceptual mechanism when colour is being processed Backhaus 1991;Reser et al 2012), and since this factor correlates with purity, it is reasonable to remove this potential factor from the model whilst retaining purity. Furthermore, studies on bumblebee (Lunau 1990;Lunau et al 1996;Rohde et al 2013) and honeybee ) perception show that for similar colours, purity is an honest signal that some bee pollinators do show an innate preference towards; therefore, it is biologically relevant to retain this factor and remove the correlating factor of chromatic contrast from the model.…”
Section: Effects Of Visual Appearancementioning
confidence: 99%
“…For honeybees and bumblebees, there exist detailed data on how receptor signals facilitate colour processing at a neural level by opponent mechanisms in the brain (Kien and Menzel 1977;Yang et al 2004;Paulk et al 2009;Dyer et al 2011) which facilitates trichromatic colour perception as demonstrated in behavioural experiments (von Frisch 1914;Daumer 1956;von Helversen 1972;Giurfa 2004;Dyer et al 2008;Reser et al 2012). This detailed knowledge has allowed for the development of colour space models Chittka 1992;Vorobyev and Brandt 1997;Kemp et al 2015) to facilitate analyses of how flower signals are distributed in different environments (Chittka et al 1994;Chittka and Wells 2004).…”
Section: Introductionmentioning
confidence: 99%